Effect of Zuo's warming Yang acupuncture therapy combined with lifestyle interventions on prediabetes: A randomized controlled trial - Yang Li; Kehang Xie; Xuanli Zeng; Lu Ding; Yuting Wang; Liming Lu; Changbo Zuo (Elsevier, 2023)
Background: Acupuncture has promising effects on diabetes, but there is limited evidence on prediabetes. The purpose of this study was to evaluate the effect and safety of Zuo's warming Yang acupuncture therapy on prediabetic patients. Methods: Fifty five individuals with prediabetes were recruited for the study. Participants in the non-acupuncture group received a 12-week lifestyle intervention, while those in the acupuncture group received the same lifestyle intervention in addition to two 50-minute sessions of Zuo's warming Yang acupuncture therapy per week. The primary outcomes measure fasting plasma glucose (FPG), 2-hour postprandial glucose (2hPG), and Glycated hemoglobin determination (HbA1c) after 12 weeks of treatment. Results: Both acupuncture group and non-acupuncture group showed significant reductions in FPG and 2hPG levels after treatment, with a statistically significant difference between them (FPG:6.25 ± 0.48 vs 5.73 ± 0.50, P < 0.001; 6.21 ± 0.42 vs 6.04 ± 0.41, P = 0.035; 2hPG:8.90(8.44,9.88) vs 7.95(6.93,8.34), P < 0.001; 9.22 ± 1.15 vs 8.70 ± 1.34, P = 0.046; respectively). In addition, FPG and 2hPG in the acupuncture group decreased more significantly than those in the non-acupuncture group after treatment, and the difference was statistically significant (FPG:5.73 ± 0.50 vs 6.04 ± 0.41, P = 0.014;2hPG:7.95(6.93,8.34) vs 8.70 ± 1.34, P = 0.015; respectively). Although both groups showed reductions in HbA1c, only the decrease in the acupuncture group was statistically significant(5.80(5.60,5.90) vs 5.60(5.40,5.80), P = 0.015). No severe adverse events were reported. Conclusions: Zuo's warming Yang acupuncture therapy conjunction with lifestyle interventions was more effective than lifestyle interventions alone in reducing FPG, 2hPG and HbA1c levels in prediabetic patients. These results suggest that Zuo's warming Yang acupuncture therapy may be a safe and effective treatment option for prediabetes.